An Optimal State Feedback Controller Based Neural Networks for Synchronous Generator Excitation Control System - Moath Hasan Al-qatamin (International Journal of Electrical and Computer Engineering (IJECE), 2013)
In this paper, an artificial neural network (ANN) is designed to optimize thematrix gain of state feedback controller. A linear mathematical model of asynchronous generator with excitation system is used as controlled system.The conventional methods that used to find the matrix gain need tediouscalculations with compared to neural networks. The simulation proves thatthe proposed feedback controller based neural network optimization method has the better result in order to prove the dynamic performance of a single machine connected to infinite bus system(SMIB). The robustness of the proposed controller is tested by disturbance in excitation voltage. The results are compared with results of controller based on conventional methods. Thepotentials of the proposed technique are investigated using MATLAB software.DOI:http://dx.doi.org/10.11591/ijece.v3i4.3125